A goal programming approach for frozen food production planning / Aishah Mahat ... [et al.] - Mahat, Aishah; Mohd Zaki, Norwahyu; Teoh, Yeong Kin; Hasmy, Harshida; Ahmad, Nur Intan Syafinaz (UiTM Cawangan Perlis, 2022)
This paper examines the Goal Programming (GP) approach in food production planning in order to further enhance and find better solutions. The objective of this paper is to determine the optimum level of frozen food production for small and medium enterprise (SME). Azali Frozen Food, a small and medium enterprise located in Penang was selected as it can produce a range of frozen foods throughout the country. The problem is handled through Lexicographic Goal Programming. The results are compared to the available data that was given and other findings were reviewed. The findings of this paper are expected to assist community small and medium enterprise and other decision makers involved in production planning. The developed method will also be of use for those who are interested in the model of goal programming to solve complex planning issues involving uncertain parameters.